Enterococcal - associated vertebral osteoarthritis (Evoa) in broiler chicken in Malaysia : a case report - Basit Zeshan; Khaing A.T; Nur Hardy Abu Daud (2015)
Enterococcus cecoruminfection is an emerging pathogen of poultry causing femoral head necrosis and spondylitis increasingly been described in various countries over the past decade. This case report describes the first outbreak of clinical enterococcal related osteoarthritis in chicken flocks in Malaysia. In May, 2015, a 4-week- old broiler chicken flock in Kelantan, Malaysia displayed a veriety of clinical signs, including swollen, inflamed hocks, hock sitting, lameness, paresis or complete paralysis, with greenish white diarrhoea and mortality rate of 5% at day 36 post hatch.